Lead (Pb) Accumulation by Typha angustifolia and Cyperus alternifolius in a Constructed Wetland System - Nilam Kinanti; Intan Permata Hadi (Open Global Scientific Journal, 2026)
Background: Lead (Pb) is one of the most common heavy metal contaminants in aquatic environments due to its extensive use in industrial activities. In developing countries such as Indonesia, wastewater treatment facilities often have limited capacity to effectively process industrial effluents, leading to the release of Pb-contaminated wastewater into the environment.Aims: This study aimed to evaluate the Pb accumulation potential and phytoremediation performance of Typha angustifolia and Cyperus alternifolius in a laboratory-scale constructed wetland system operated under a static batch method for the remediation of Pb-contaminated water.Methods: The experiment consisted of a control treatment without plants and two plant species exposed to three Pb concentrations (10, 20, and 30 mg L⁻¹). Water temperature, water pH, soil pH, and Pb concentrations in water, soil, and plant tissues were measured. Temperature and pH were recorded at 1 and 14 days after planting, while Pb concentrations were analyzed at the end of the 14-day experimental period. The phytoremediation potential of both plant species was evaluated using the Bioconcentration Factor (BCF) and Translocation Factor (TF).Results: The results showed that the constructed wetland system effectively reduced Pb concentrations in water, with removal efficiencies ranging from 85% to 96%. However, the soil have big contribution in removal Pb in water. T. angustifolia demonstrated BCF and TF values greater than 1 across all Pb concentrations, indicating strong accumulation and translocation abilities. In contrast, C. alternifolius exhibited BCF values below 1 but TF values greater than 1, suggesting limited accumulation capacity with effective Pb translocation from roots to shoots.Conclusion: Both species have potential for application in constructed wetland systems for Pb remediation, with T. angustifolia showing superior phytoremediation performance.